Biochemical Characterization of Brinjal (Solanum melongena L.) Leaves Infected with Little Leaf Disease - B. P. Chauhan; Y. M. Shukla; Urja B. Solanki; J. J. Dhruv (International Journal of Economic Plants)
The experiment was conducted during September, 2023 to February, 2024 at the Department of Biochemistry, Anand Agricultural University, Anand, Gujarat, India. Total 28 genotype originating from a cross between a little leaf resistance parent AB 15-06 (S. melongena) and a susceptible parent GRB 5 (S. melongena). Disease incidence recorded from 14 each of highly resistant and susceptible genotypes and their parents AB 15-06 (Resistance against little leaf disease) and GRB 5 (Susceptible against little leaf disease) were selected for biochemical attributes comprised of chlorophyll (0.73–0.98 mg g-1), moisture (76.77–97.43%), phenol (0.43–3.26 mg g-1), total soluble sugar (2.36–4.57 mg g-1), membrane injury (24.56–69.87%). Correlation analysis of biochemical characters like chlorophyll and moisture were observed negatively correlated with disease incidence while rest of biochemical parameters total soluble solids, membrane injury and phenol content were positively correlated. Membrane injury (0.254), moisture (0.026), TSS (0.030), and phenol content (0.016) showed positive skewness whereas chlorophyll (-1.318), membrane injury (-1.540), moisture (-1.543), total soluble sugar (-1.160) and phenol content (-1.626) detected negative kurtosis. GCV, PCV and heritability analysis for all biochemical characters recorded were chlorophyll (36.46%, 36.5% and 99.82%), membrane injury (61.52%, 61.96% and 98.59%), moisture (7.55%, 8.73% and 13.44%), total soluble sugar (99.39%) and phenol content (46.76%, 46.83% and 99.67%).